Blount disease and familial inheritance in Ghana, area cross-sectional study - Freek Hollman; Niels Jansen; Frans Bovendeert; Prosper Moh; Alexander Stegmann; Heleen M Staal (BMJ Publishing Group, 2021)
Objective The objective of this study is to study familial inheritance for Blount disease to create better understanding of the aetiology of Blount disease.Methods After reviewing patient files and conventional roentgenologic imaging, 139 patients with Blount disease were included in this cross-sectional study, of which 102 patients were interviewed. During the interviews, patient characteristics and family history were collected. Blood samples were taken from five patients and three families and a whole exome sequencing was performed.Results Although patients came from all over the country, 90% of the patients belonged to the Akan tribe. A positive family history was found in 63 families (62%), of which, almost two-third had a positive family history in a first-degree family member. In most of the cases (64%), the varus legs resolved over time. In 9%, severe bowing remained 'just like the patient'. The results of the whole exome sequencing did not show a genetic predisposition.Conclusion This study describes a large group of Blount patients. Because of the high numbers of positive family history and the centralisation of patients in the Akan region, a familial predisposition is suggested. Further genetic research is essential for better understanding of the possible multifactorial aetiology in Blount disease.